2017
DOI: 10.1039/c6py01736c
|View full text |Cite
|
Sign up to set email alerts
|

New insight into the polymerization mechanism of 1,3-dienes cationic polymerization. IV. Mechanism of unsaturation loss in the polymerization of isoprene

Abstract: The mechanism of obtaining a polymer with reduced unsaturation is proposed, which includes the formation of branched structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 43 publications
2
23
0
Order By: Relevance
“…The similar higher content of head groups as compared to end groups was observed for other "cationic" poly(1,3-diene)s. [17,18,28,42,43] These observations are consistent with the side reaction, which consists in the transfer of growing polymer chain to the double bond of "own" or "alien" macromolecule with the formation of trifunctional branched point and release of the proton. [41] In this case, the obtained branched macromolecule can contain several head groups [41,43,44] and does not contain any chlorine-terminated chain ends due to the absence of termination via ion pair collapse.…”
Section: Timentioning
confidence: 99%
“…The similar higher content of head groups as compared to end groups was observed for other "cationic" poly(1,3-diene)s. [17,18,28,42,43] These observations are consistent with the side reaction, which consists in the transfer of growing polymer chain to the double bond of "own" or "alien" macromolecule with the formation of trifunctional branched point and release of the proton. [41] In this case, the obtained branched macromolecule can contain several head groups [41,43,44] and does not contain any chlorine-terminated chain ends due to the absence of termination via ion pair collapse.…”
Section: Timentioning
confidence: 99%
“…The COC bond formation was also observed as a minor product in the polymerized material (Scheme ). Possibilities for this observation are macrocyclic compound formation and crosslinking.…”
Section: Resultsmentioning
confidence: 99%
“…The C O C bond formation was also observed as a minor product in the polymerized material (Scheme 2). Possibilities for this observation are macrocyclic compound formation [15] and crosslinking. Reinvestigation of the samples was carried out after the irradiation process and it was confirmed that the materials were further cured due to gamma radiation without deteriorating (Fig.…”
Section: Nmr Analysismentioning
confidence: 97%
See 1 more Smart Citation
“…Conjugated double bonds (trans) in unsaturated side chain of laccol and terminal double bond in limonene was involved prominently during the chain growth polymerization. Additionally, as explained by Rozentsvet et al [16] macrocyclic compound formation is also possible due to the phenate ions and cis/trans double bonds (unsaturated groups) in the laccol side chain. These phenomena were clearly observed in the infrared and nuclear magnetic resonance (NMR) data obtained for the synthesized copolymers.…”
Section: Introductionmentioning
confidence: 93%